The Possible Effects of Altitude and Climate on the Development of the Frontal Sinus in Adults - Asirdizer,Mahmut (Sociedad Chilena de Anatomía, 2017)
Climatic and altitude features of living region may affect human body. Many changes in several tissues and organs and several health problems due to climatic and altitude effects were defined in the literature. However, there were limited number of studies which evaluated correlation between development of frontal sinus and climatic/altitude effect. In this study, widths, heights, AP lengths and volumes of frontal sinus were compared by Paranasal CT scans in populations living in Van which has colder climate and higher altitude and Manisa which has milder climate and lower altitude. It was found that widths, antero-posterior lengths and volumes of frontal sinus were higher in populations living in colder climate and higher altitude according to populations living in milder climate and lower altitude. Heights of frontal sinuses were on the contrary of this. These results were found appropriate to increasing of cephalic index in cold climate according to Allen's Rule. We suggest that larger population study should be made with peoples having the same or similar race and genetic structure in different climate and altitude regions and the proportional comparison of frontal sinus measurements with cephalic index should be considered in future studies.